COMPARATIVE ANALYSIS OF CUSTOMER SATISFACTION BETWEEN PREPAID AND POSTPAID ELECTRICITY IN MANADO - Rumengan, Natasya S.; Kindangen, Paulus; Pandowo, Merinda H. C. (Universitas Sam Ratulangi, 2021)
There are still many people who are loyal and do not want to switch to prepaid electricity services, this can happen because of the excess of postpaid electricity is that people do not need to get ready to buy electric pulses because the electricity is always available and also not all people especially the household sector have high incomes and must at any time have the funds to buy electricity pulse when the pulse electricity runs out. The purpose of this research is to know the comparison of customer satisfaction on prepaid electricity and postpaid electricity in Manado. This study uses quantitative research and Independent Sample T-test as a tool to analyze the data that has been collected from questionnaire that distributed to 100 respondents as sample of this research. The findings of this study show that there are differences of customer satisfaction from different users. Based on the result, the researcher provided several recommendations which are: making improvement regarding the machines which can be considered as old and change it into a new one, do evaluation regarding errors that may happen and do prevention regarding the errors, also have check and balance system regarding the amount of electricity in order to prevent shortage of power.Â Keywords: customer satisfaction, comparative analysis, service quality, product quality, price